2021
DOI: 10.1186/s12284-021-00515-7
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Doubling Event Reshapes Rice Morphology and Products by Modulating Chromatin Signatures and Gene Expression Profiling

Abstract: Evolutionarily, polyploidy represents a smart method for adjusting agronomically important in crops through impacts on genomic abundance and chromatin condensation. Autopolyploids have a relatively concise genetic background with great diversity and provide an ideal system to understand genetic and epigenetic mechanisms attributed to the genome-dosage effect. However, whether and how genome duplication events during autopolyploidization impact chromatin signatures are less understood in crops. To address it, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The number of ACRs and the total sequence length of the hybrids were significantly larger than those of the parents, indicating more robust chromatin accessibility of the hybrid genomes. By comparing the ATAC-seq data of multiple plant genomes reported previously (Lu et al, 2019;Schwope et al, 2021;Zhou et al, 2021), the genome proportion of ACRs in tea plants was much lower than that of plants with smaller genomes such as Spirodela polyrhiza, Arabidopsis thaliana, Eutrema salsugineum and Vitis vinifera, but higher than that of Hordeum vulgare (Figure 4b). We further examined the distribution of ACRs in the tea plant genome and classified them as gACRs (genic ACRs in exons, introns and UTRs), pACRs (proximal ACRs within 2 kb upstream of the TSS and 2 kb downstream of the TTS) and dACRs (distal ACRs in the intergenic).…”
Section: Features Of Chromatin Accessibility In Tea Hybrids and Their...mentioning
confidence: 72%
“…The number of ACRs and the total sequence length of the hybrids were significantly larger than those of the parents, indicating more robust chromatin accessibility of the hybrid genomes. By comparing the ATAC-seq data of multiple plant genomes reported previously (Lu et al, 2019;Schwope et al, 2021;Zhou et al, 2021), the genome proportion of ACRs in tea plants was much lower than that of plants with smaller genomes such as Spirodela polyrhiza, Arabidopsis thaliana, Eutrema salsugineum and Vitis vinifera, but higher than that of Hordeum vulgare (Figure 4b). We further examined the distribution of ACRs in the tea plant genome and classified them as gACRs (genic ACRs in exons, introns and UTRs), pACRs (proximal ACRs within 2 kb upstream of the TSS and 2 kb downstream of the TTS) and dACRs (distal ACRs in the intergenic).…”
Section: Features Of Chromatin Accessibility In Tea Hybrids and Their...mentioning
confidence: 72%
“…This hypothesis is supported by several studies in plants. For example, a study in rice showed that induced chromatin accessibility leads to preferential recruitment of H3K36me2 and H3K36me3 ( 89 ). In Arabidopsis , genome duplication can contribute to the switching of some loose and compact structural domains and altered H3K4me3 and H3K27me3 modification ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 2021 ) found that polyploidy induces DNA hypomethylation and salt stress-induced hypermethylation to repress proximal TEs and/or TE-associated stress-responsive genes in 4X of two japonica varieties (Wang et al 2021 ). Autopolyploids lead to a higher number of accessible chromatin regions (ACRs) in euchromatin, and modulate chromatin signatures and transcriptional profiling (Zhou et al 2021 ). The results suggested that chromosome doubling magnified genomic instability, epigenetic variability and chromatin accessibility.…”
Section: Discussionmentioning
confidence: 99%